Optimised transcranial direct current stimulation (tDCS) for fibromyalgia—targeting the endogenous pain control system: a randomised, double-blind, factorial clinical trial protocol - Luis Castelo-Branco; Elif Uygur Kucukseymen; Dante Duarte; Mirret M El-Hagrassy; Camila Bonin Pinto; Muhammed Enes Gunduz; Alejandra Cardenas-Rojas; Kevin Pacheco-Barrios; Yiling Yang; Paola Gonzalez-Mego; Anayali Estudillo-Guerra; Ludmilla Candido-Santos; et al. (BMJ Open)
Introduction Fibromyalgia (FM) is a common debilitating condition with limited therapeutic options. Medications have low efficacy and are often associated with adverse effects. Given that FM is associated with a defective endogenous pain control system and central sensitisation, combining interventions such as transcranial direct current stimulation (tDCS) and aerobic exercise (AE) to modulate pain-processing circuits may enhance pain control.Methods and analysis A prospective, randomised (1:1:1:1), placebo-controlled, double-blind, factorial clinical trial will test the hypothesis that optimised tDCS (16 anodal tDCS sessions combined with AE) can restore of the pain endogenous control system. Participants with FM (n=148) will undergo a conditioning exercise period and be randomly allocated to one of four groups: (1) active tDCS and AE, (2) sham tDCS and AE, (3) active tDCS and non-aerobic exercise (nAE) or (4) sham tDCS and nAE. Pain inhibitory activity will be assessed using conditioned pain modulation (CPM) and temporal slow pain summation (TSPS)—primary outcomes. Secondary outcomes will include the following assessments: Transcranial magnetic stimulation and electroencephalography as cortical markers of pain inhibitory control and thalamocortical circuits; secondary clinical outcomes on pain, FM, quality of life, sleep and depression. Finally, the relationship between the two main mechanistic targets in this study—CPM and TSPS—and changes in secondary clinical outcomes will be tested. The change in the primary efficacy endpoint, CPM and TSPS, from baseline to week 4 of stimulation will be tested with a mixed linear model and adjusted for important demographic variables.Ethics and dissemination This study obeys the Declaration of Helsinki and was approved by the Institutional Review Board (IRB) of Partners Healthcare under the protocol number 2017P002524. Informed consent will be obtained from participants. Study findings will be reported in conferences and peer-reviewed journal publications.Trial registration number NCT03371225.